Implementasi Data Mining Menggunakan Algoritma J48 Dalam Menentukan Pola Itemset Belanja Pembeli (Study Kasus: Swalayan Brastagi Medan) - Nurmita Sari Pakpahan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Brastagi supermarket is a shop that sells all kinds of daily needs. In determining the number of goods, Brastagi supermarkets in Medan are still experiencing very heavy obstacles because so far they are still using very simple applications in managing sales data. Based on this, the researcher is interested in a search for patterns of buyers' shopping itemset from large-scale data and that associates data with one another using the Decision tree j48 algorithm. So that it can assist in making decisions on determining the amount of goods to be provided, because the quality of the company is judged by the seriousness in managing sales data. The purpose of this study is to determine the pattern of the buyer's shopping itemset, which items are often purchased and later the company can make decisions to increase sales of these goods.